Role of "well known" proteins on cell wall degradation and softening - Vicente, Ariel Roberto; Rodoni, Luis Maria; Salato, Gloria Silvia; Basanta, Maria Florencia; Ponce, Nora Marta Andrea; Stortz, Carlos Arturo; Raffo Benegas, Maria Dolores; Powell, Ann L.T.; Bennett, A.B.; Labavitch, John Marcus (International Society for Horticultural Science, 2024)
Trabajo presentado al V International Conference Postharvest Unlimited, Chipre, 2015